Real-Time PCR Assay of Individual Human Immunodeficiency Virus Type 1 Variants in Coinfected Human Lymphoid Tissues - Ito, Yoshinori (American Society for Microbiology, 2003)
In the course of infection, human immunodeficiency virus type 1 (HIV-1) mutates, diverging into a “swarm” of viral quasispecies, and the predominance of CCR5- or CXCR4-utilizing quasispecies is strongly associated with the pattern of disease progression. Quantification of CCR5- and CXCR4-utilizing viruses in viral swarms is important in the investigation of the mechanisms of this phenomenon. Here, we report on a new real-time PCR-based methology for the evaluation of replication of individual CCR5- and CXCR4-utilizing variants. The assay is highly reproducible, with a coefficient of variation of <3%, and it accurately estimates the numbers of virus-specific RNA copies even when their difference in the mixture is 2 orders of magnitude. We demonstrate that replications of CCR5- and CXCR4-utilizing variants can be evaluated and distinguished in experimentally coinfected human lymphoid tissue. The assay we developed may facilitate study of the mechanisms of the R5-to-X4 switch in viral swarms in human tissues infected with HIV-1.